PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI - Defriavi Kavela (Universitas Slamet Riyadi, 2016)
The purpose of this study was to analyze the significance of the effect of the work environment and motivation to employee performance and analyze the effect of the work environment on employee performance mediated by motivation. This study is a survey of staff at the Department of Cleanliness And Landscaping Surakarta. The study population and sample as many as 421 people were taken as many as 85 people with proportional cluster random sampling technique. The type of data used quantitative and qualitative data. Sources of data used primary data and secondary data. The technique of collecting data used questionnaires, observations and literature. Data were analyzed used validity, reliability, classic assumption test and path analysis. The survey results revealed that the work environment has a significant effect on employee performance. Work environment has a significant effect on employee motivation. Motivation has no significant effect on the employee performance. Motivation does not mediate the effect of the work environment on employee performanceKeywords: work environment, motivation, performance.